TETANIC CRISIS IN EMERGENCY CARDIOLOGY - DIFFICULTIES DIFFERENTIAL DIAGNOSIS OF ACUTE CORONARY SYNDROME - V. V. Rezvan; D. Y. Spirochkin; A. V. Magnitsky; O. N. Rumyantsev (SINAPS LLC, 2016)
The report presents a case of tetanic crisis in a patient with postoperative parathyroid insufficiency after strumectomy that emergency doctors were interpreted as an acute coronary syndrome with collapse.